2006
DOI: 10.1593/neo.06625
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Detection of TMPRSS2:ERG Fusion Transcripts in the Urine of Men with Prostate Cancer

Abstract: We recently reported the identification of recurrent gene fusions in the majority of prostate cancers involving the 5' untranslated region of the androgen-regulated gene TMPRSS2 and the ETS family members ERG, ETV1, and ETV4. Here we report the noninvasive detection of these gene fusions in the urine of patients with clinically localized prostate cancer. By quantitative polymerase chain reaction, we assessed the expression of ERG and TMPRSS2:ERG transcripts in urine samples obtained after prostatic massage fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
153
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(166 citation statements)
references
References 12 publications
9
153
0
4
Order By: Relevance
“…Several studies to date have demonstrated the detection of the TMPRSS2:ERG fusion transcripts in urine. 44,45,67 These studies, and other unpublished reports, demonstrate a high specificity. Unlike PSA, which can be elevated in benign conditions as well as cancer, the presence of TMPRSS2:ERG transcripts has only been reported in neoplastic cells.…”
Section: Diagnostic and Clinical Therapy Implicationssupporting
confidence: 77%
See 1 more Smart Citation
“…Several studies to date have demonstrated the detection of the TMPRSS2:ERG fusion transcripts in urine. 44,45,67 These studies, and other unpublished reports, demonstrate a high specificity. Unlike PSA, which can be elevated in benign conditions as well as cancer, the presence of TMPRSS2:ERG transcripts has only been reported in neoplastic cells.…”
Section: Diagnostic and Clinical Therapy Implicationssupporting
confidence: 77%
“…This has important clinical implications, as the TMPRSS2:ERG transcript can be detected in urine and represents a highly specific prostate cancer biomarker. [44][45][46] The common ETS gene fusions are widely believed to have an important oncogenic role, but that ERG or ETV1 overexpression alone is not sufficient to lead to prostate cancer. There is now mounting molecular data for an important concomitant role of TMPRSS2:ERG and the pten/PI3K/ATK pathway activation in prostate cancer oncogenesis.…”
Section: A Multitude Of Gene Fusions In Prostate Cancermentioning
confidence: 99%
“…69 Urine RNA was analyzed by qRT-PCR after preamplification (whole transcriptome amplification) and then break-apart fluorescent in situ hybridization (FISH) was used to validate the presence or absence of the TMPRSS2/ERG gene rearrangement in the CaP tissue. Indeed, patients with high levels of ERG and detectable levels of TMPRSS2/ERG in their urine were positive for ERG rearrangement.…”
Section: Gene Fusions In Prostate Cancermentioning
confidence: 99%
“…Current biopsy strategies may miss heterogenous tumor foci, and urine-based assay would have a great advantage because the cells from multiple cancerous foci of whole prostate could be released and collected. 69 Laxman et al 12 reported that a multiplex panel of urine transcripts outperforms PCA3 transcript and serum PSA alone in detecting CaP. Expression of seven putative prostate cancer biomarkers was measured (PCA3, PSA, GOLPH2, SPINK1, AMACR, TMPRSS2/ERG, TFF3) by qRT-PCR in urine samples.…”
Section: Multiplex Analysis Of Urine Markers and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation